Analysis Guilt Development of Regan's in A Quiet Place Movie Script - Kostavialdus Setiadi; Rindrah Kartiningsih (PT. Padang Tekno Corp, 2025)
Guilt is a complex emotional experience that arises when someone violated social moral standards. This study focuses on how Regan's guilt is depicted, the causes of guilt, and the negative effects of guilt on behavior. This study uses a qualitative description method with a moral psychology approach, as well as literature studies to examine film scripts and academic sources relevant to the topic being analyzed. The results of this study are Regan's guilt arises from violations of family rules, the psychological causes of this guilt include reciprocal moral violations, feelings of ostracism, the desire to punish oneself, deep empathy, and loss of self-control. This study also shows the negative effects of guilt on behavior, including withdrawal, submission, and self-punishment. This study contributes to the study of literary psychology through in-depth character analysis based on emotional and moral aspects.